Integration of Feed Nutrient Analysis and Predictive Model in Assessing the Performance of Native Chickens fed with Rhizopus sp. Fermented Rice Bran - Ginting, Risdawati; Supiyandi; Marlina, Leni; Ginting, Giovany (Journal of Computer Science, Artificial Intelligence and Communications, 2025)
The study aimed to determine the effect of giving fermented rice bran with Rhizopus sp on the performance of free-range chickens. This study used a non-factorial Complete Random Design (RAL) method with 4 treatments and 5 replicates. The treatment used was as follows: P0 = control, P1 = ration + 10% DPF, P2 = ration + 15% DPF and P3 = ration + 20% DPF. The results of the study showed that the administration of fermented rice bran can affect the performance of free-range chickens, namely ration consumption, body weight gain, and ration conversion. The results of the fingerprint analysis showed that the P2 treatment (ration + 15% DPF) had a conversion of 3.64 and the highest body weight gain of 63.81 g.